Entrectinib can induce nerve cell damage by inhibiting PI3K-AKT and TGF-β signaling pathways - Tang, Qingshan; Dong, Jiachen; Zhang, Feng; Zhao, Dan; Yang, Qi; Wen, Jiayu; Sun, Yuhao; Wei, Jifu; Liu, Zhixian (Frontiers in Pharmacology, 2025)
BackgroundThe tyrosine receptor kinase inhibitor (TRKi) entrectinib is used to treat neurotrophic tyrosine receptor kinase (NTRK) fusion-positive solid tumors and ROS1-positive patients. Despite its impressive efficacy against cancer, the clinical application is still limited by the central nervous system (CNS)-related toxicities. However, the precise mechanism of such CNS-related toxicities remains elusive.MethodsThe effect of entrectinib-induced nerve cell damage was evaluated by the nerve cells (PC12, HT22 and SK-N-SH) based in vitro models. Various assays, including CCK-8, colony formation and EdU incorporation assays were utilized to estimate the cellular viability and proliferation ability. Cell apoptosis was measured by flow cytometry. Next, transcriptome sequencing technology was performed to identify differentially expressed genes (DEGs). Gene ontology (GO), kyoto encyclopedia of genes and genomes (KEGG) analysis and gene set enrichment analysis (GSEA) were applied to predict the potential functions of DEGs. Quantitative real time polymerase chain reaction (qRT-PCR) and Western blotting assays were performed to measure the expressions of thrombospondin-1 (THBS1), TGF-β1, PI3K, AKT and phosphorylated AKT (p-AKT) in the entrectinib-treated nerve cells. Additionally, we Preliminary observed and validated whether THBS1 overexpression could rescue nerve cell damage and the abnormalities in PI3K-AKT and TGF-β signaling pathways.ResultsEntrectinib significantly inhibited the nerve cells proliferation and colony formation, and induced nerve cells apoptosis. Transcriptome sequencing analysis and qRT-PCR revealed that THBS1 was downregulated within entrectinib treatment. KEGG and GSEA analysis also suggested that entrectinib directly caused the abnormalities in proliferation-related signaling pathway like PI3K-AKT pathway, and apoptosis-related signaling pathway including TGF-β pathway. We further demonstrated that THBS1, TGF-β1, PI3K, AKT and p-AKT were downregulated by entrectinib. Meanwhile, pretreatment with THBS1 overexpression plasmids significantly rescued nerve cells (PC12, HT22 and SK-N-SH) from cell death and the abnormalities in PI3K-AKT and TGF-β signaling pathways.ConclusionThese results identified a critical role of entrectinib in promoting nerve cell damage by downregulating the expression of THBS1 while also inhibiting PI3K-AKT and TGF-β signaling pathways. Our findings will provide potential therapeutic targets for CNS-related toxicities.